CHARACTERRISTICS OF MORPHOFUNCTIONAL CHANGES IN THE TESTIS CAUSED BY HYDROCELE - Grytsuliak, B.V.; Spaska, A.M.; Grytsuliak, V.B.; Yvasyuk, I.I.; Dolynko, N.P. (World of Medicine and Biology, 2014)
In our investigation we used ultramicroscopy for analyses of convoluted semoniferous tubules structure and Leydig cells (interstitial endicrynocytes) in adult men of reproductive age, who suffered hydrocele testis. It was discovered that hydrocele testis caused almost double decrease of testicular volume, of seminiferous tubules diameter, number of cells in spermatogenic epithelium and of Leydig cell’s nuclei volume. All of this was caused by significant ultrastructural changes in the wall of hemocapillaries, in lamina propria of seminiferous tubules, in tight junctions between Sertoli cells (epitheliocytes). The shown changes approve the necessity of early treatment for hydrocele.